2021
DOI: 10.48550/arxiv.2111.12577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Method for Evaluating the Capacity of Generative Adversarial Networks to Reproduce High-order Spatial Context

Abstract: Generative adversarial networks (GANs) are generative models with the potential to revolutionize biomedical imaging. The overarching problem with GANs in clinical applications is a lack of adequate or automatic means of assessing the diagnostic quality of images generated by GANs. We demonstrate several statistical tests of images output by two popular GAN architectures. We designed several stochastic object models (SOMs) of distinct features that can be recovered after generation by a trained GAN. Several of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Although the FID score has shown excellent agreement with subjective visual assessments by humans [28], it is agnostic to the downstream task a medical image GAN may be used for. Additionally, it is an ensemble statistic, and hence could be blind to specific errors in high-order statistics of individual images [29].…”
Section: Evaluation Of Generative Adversarial Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the FID score has shown excellent agreement with subjective visual assessments by humans [28], it is agnostic to the downstream task a medical image GAN may be used for. Additionally, it is an ensemble statistic, and hence could be blind to specific errors in high-order statistics of individual images [29].…”
Section: Evaluation Of Generative Adversarial Networkmentioning
confidence: 99%
“…Furthermore, the above mentioned measures are ensemble measures. It has been shown that individual samples drawn from the GAN may contain impactful errors despite giving satisfactory ensemble measures [29]. Lastly, medical image distributions typically consist of multiple classes or modes, and it has been shown that may produce critical errors while producing images from a mode that is rarely seen during training [18].…”
Section: Introductionmentioning
confidence: 99%
“…The StyleGAN must be sufficiently welltrained and should accurately represent the to-be-imaged object distribution. This can be challenging in diagnostic imaging applications, where the objects can contain varying pathologies that may not be fully represented in the StyleGAN training data [43], [44]. As such, the representation error of the Style-GAN should be acknowledged when employing PULSE++.…”
Section: B Ct Imaging System With Limited Angular Rangementioning
confidence: 99%
“…Despite the apparent realism and diversity in images, the extent to which a GAN learns image statistics is still an ongoing topic of research. [17][18][19] In particular, image GANs may produce images that appear visually realistic, but possess ensemble statistics that are incorrect, 19 which could be detrimental to downstream applications. 20 The Frechet inception distance (FID) score, inception score (IS) and average log-likelihood are a few among a long list of metrics that have been proposed to evaluate GANs.…”
Section: Purposementioning
confidence: 99%